Pengembangan Search Engine Konten Statistik pada Website Badan Pusat Statistik untuk Mendukung Diseminasi Statistik Resmi - Yohanes Wahyu Trio Pramono; Dhoni Eko Wahyu Nugroho (Politeknik Statistika STIS, 2022)
BPS as a government-owned public agency, has the duties and authorities as an official body that disseminates statistical data. With the increasing penetration of internet usage, the website channel is one of the electronic media that is fast and easy to answer the challenges of data dissemination strategies. The development and implementation of a search engine on the BPS website have now succeeded in providing a search function for diverse statistical content, across website domain areas, and capable of performing image searches using image-to-text techniques and in-depth searches of all PDF texts for PDF publications and Official News Statistics PDF format. With this search engine development strategy, it is hoped that the data dissemination business process at the BPS Dissemination Directorate can run more optimally, being able to provide the data desired by data users more easily, quickly, and precisely.